Bioactivity of 11 keto and hydroxy androgens in yeast and mammalian host cells. Issue 218 (April 2022) - Handelsman, David J.; Cooper, Elliot R.; Heather, Alison K.
Highlights: 11 keto or hydroxy androgens circulate at levels like testosterone in women. Androgenic bioactivity was evaluated using in vitro yeast or mammalian host cells. Mammalian host cells are more sensitive and yeast host cells more specific. 11 keto derivatives had lower androgenic potency than their parent androgens. 11 hydroxy derivatives had minimal or no androgenic bioactivity. 5α reduction increased androgenic potency. Abstract: Recent studies have highlighted the potential role of 11oxygenated (keto or hydroxy) androgens in human reproductive function with 11keto androgens circulating at concentrations comparable with testosterone in women and children. However, the intrinsic androgenic bioactivities of 11 keto and hydroxy androgens are not fully characterized. We therefore investigated the full androgen dose-response curves using complementary in vitro yeast and mammalian (HEK293) host cell bioassays of 11 keto and hydroxy derivatives of the potent androgens, testosterone (T) and dihydrotestosterone (DHT), compared with their parent non-11 oxygenated steroids together with the pro-androgen precursor (androstenedione (A4 )) and metabolites (androstanedione, androsterone). For potent androgens, the mammalian HEK293 host cell bioassay was 22–138 times more sensitive than the yeast host cell bioassay. In both androgen bioassays, 11keto derivatives displayed androgenic bioactivity but significantly lower molar potency than their parent non-keto steroids. By contrast, the 11hydroxy derivatives had minimal or no androgenic bioactivity. In both bioassays 5α-reduction increased androgenic potency. These findings confirm that that 11keto androgens may contribute directly to androgen status in women, children, and other conditions apart from healthy eugonadal men whereas 11hydroxy androgens have negligible androgenic potency although it cannot be excluded that they may be converted to more potent androgens in vivo .